Візантійські та угорські монети з Чорнівського городища - Калініченко, Віталій; Ільків, Микола; Пивоваров, Сергій (Львів, Видавничий центр Львівського національного університету імені Івана Франка, 2016)
To one of the most studied ancient monuments watershed of the Upper Prut and Middle Dniester refers settlement (remnants of feudal fortified manor) is located at a distance of 5 km south of the village Chornivka. In historiography it is known as Chornivka hillfort. Study of the settlement began in 1999 and continues to date. According to a new period of excavations monuments significantly refined its planning, functional identity revealed some structures defined their chronology and dating, found more than a thousand individual finds. Among the found materials research settlement in 1999–2014 on special interest deserve found numismatic items. There are four Byzantine and four Hungarian coins. It’s comprehensive analysis and interpretation and publication devoted to this. The first coins of the concave-convex a surface. It’s diameter is 2,2–2,5 cm, weight – 1,5 g. Coin perforated, that is specially punched hole and not used as a banknote and a suspension icon. The detailed study of coins and search for analogies possible to determine the type of object and numismatic time of its release. Analysis of the image on the coin and its shape shows that it has a Byzantine origin. Coin from Chornivka hillfort – aspron trachea was chased in Thessalonica, during the reign of Theodore I Komnenos-Ducas (1224–1230). Other two coins were found in 2004 and 2006. The first of these is also perforated. With care it can be attributed to the coin – aspron trachea, which was chased during the reign of Demetrius Comnenos Ducas in Thessalonica, in the 1244–1246 bigennium. Fourth numismatic finding was discovered in 2014. The coin is badly damaged, cut – septangular, perforated (with a torn hole for hanging). On the concave side (reverse) observed bust image of two figures. Convex side (obverse) heavily damaged. The diameter of the findings is 1,5–1,6 cm; weight – 0,8 g with caution, similar to other areas of Europe, including the Dumbarton Oaks, the Balkans, Bulgaria, and by their appearance suggests that coin from Chornivka hillfort was chased the reign of Alexis III Comnenos Angelus in 1195–1203 in Constantinople. Nominal coins previously defined as aspron trachea. Due to significant damage of the coin image is very difficult to trace it’s narrower period of mint and relate it to the specific type. How Byzantine coins were on Chornivka hillfort? The answer of this question is difficult today. Possible explanations of these extraordinary findings are different. The literature has repeatedly drawn attention to the likely participation of combatants Kingdom of Galicia-Volhynia in the crusades, as we find hints in written and folkloric sources. If so, some of them could bring one of the participants of the Fourth Crusade. Four other coins were found in 2006. They were lying on top of one another and were a lot of thin pressed round silver plates. After their separation (coins slightly damaged by fire) revealed that the four coins, and two types. There are several versions coin identification data types. It is believed that the coins can be minted during the reign of the Hungarian King Bela III (1172–1196) or on the board, “young king” Bela IV (1225–1270). After a detailed study of these coins and view previous findings with caution copies of data, in our opinion, should be attributed to bracteates, minted during the reign “Rex iunior” – Bela IV at a time when he was “young king” in 1225–1235. Thus, summing up, to say that the period of research Chornivka hillfort in 1999–2014 was discovered quite important numismatic material, which significantly clarifies the chronological limits of existence Chornivka hillfort and allows new positions reveal its importance for political, economic, social and cultural development of the ancient people of the Middle Dniester in the thirteenth century. Therefore, in spite of this, the study of the hillfort will be continued.
Byzantine and hungarian coins from Chornivka hillfort
Keywords: Галицько-Волинське князівство; Візантія; Угорщина; монети; Чорнівське городище